Desenvolvimento de um ambiente de simulação para um robô bípede controlado por contrapeso com movimento linear - Zanette, Cícero Luiz Alves (2021)
Bipedal robots are machines capable of performing some tasks that are considerably complicated for other robots, such as climbing stairs and overcoming small obstacles, while occupying a relatively small support area. Generally, this type of machine is controlled using a so-called pendulum movement, in which the robot swings from side to side to maintain its center of mass within the support area. This requires that the robot trajectory planning also take into account its balance, which makes the project more complex. In the present work, we sought to build a simulation environment in SIMULINK for a robot whose balance was done separately from the stride through a counterweight, making the two movements independent. The developed environment was considered well-representative through a quasi-static simulation, but the development of the control proved to be more complex than planned and it was not possible to implement it, even so, the program will allow that future works in this area can be developed more quickly due to the no need to build a prototype.